Rules of the House Family Law and Domestic Disputes in Colonial Korea - Lim, Sungyun (University of California Press, 2019)
Rules of the House examines the transformation of the Korean family during and after Japanese colonial rule. Through in-depth reading of civil litigation records, the book shows how the Japanese colonial legal system transformed Korean families from the traditional patrilineal family system into small, patriarchal households. The new domestic pattern proved remarkably durable, forming the basis of postcolonial family life. Women feature prominently in the book. Increasingly marginalized by patriarchy, women embodied the fault line between one family system as it receded and the other as it expanded under the auspices of Japanese colonial law. As a consequence, women's rights to family property, inheritance, divorce, and adoption of heirs were frequently challenged by family members. Far from being quiet victims, these women brought their cases to the colonial courts and won a surprising number of cases. The book highlights how legal discourse about women's rights in colonial civil courts articulated the transformation of the family.